Challenging tradition: the Indonesian novel Saman - Rochayah Machali,; Ida Nurhayati, (Penerbit UKM, 2005)
Indonesia has witnessed the birth of a new generation of (female) writers. Many of them are young, cosmopolitan female whose work often challenges tradition, and are quite radical at that. One such writer, Ayu Utami, had won an award for her first novel Saman. This novel has invited critics, particularly because the writer has challenged tradition, both in the theme and content as well as in narrative style. Themes such as sexuality, which had been considered taboo in the past, is explored and challenged in an almost blunt way. Her frequent references to female body parts have been most strikingly merged into her critical views on tradition. Also, her rejection of conventional ways of writing can be seen, for example, in her almost ‘stubborn’ way of switching from first person to third person on the same character in virtually the same paragraph. This, as many have said, would confuse readers. She concocts her challenges to tradition by intertwining the shifts in her narration. These two main aspects of Saman, ie content and narrative style are analysed in this article, with an emphasis on the first, as it is this aspect that most clearly reflects the writer’s break from tradition.